CHILDREN'S COGNITIVE HEALTH AND EDUCATIONAL EFFICIENCY (Eureka Journal of Education & Learning Technologies, 2026)
This article explores the concept of children's cognitive health and its deterministic role in enhancing educational effectiveness. The study examines the mechanisms of cognitive process formation through the lens of fundamental theories by U. Neisser, J. Piaget, L. Vygotsky, and A. Luria. It highlights modern neuropsychological and cognitive-behavioral strategies for addressing impairments in attention, memory, and thinking. Furthermore, the paper provides practical recommendations for developing students' intellectual potential by leveraging neuroplasticity and creating a neuro-pedagogical supportive environment.
Keywords: Cognitive health, cognitive development, intelligence, executive functions, neuroplasticity, neuropedagogy, attention deficit, zone of proximal development, mnemonics.